2022
DOI: 10.1111/jdi.13758
|View full text |Cite
|
Sign up to set email alerts
|

Living and working environments are important determinants of glycemic control in patients with diabetes during the COVID‐19 pandemic: A retrospective observational study

Abstract: Aim: To investigate (1) the association of lifestyle changes and living and working conditions with glycemic control and (2) whether treatment was intensified appropriately in patients with diabetes under the first COVID-19 state of emergency in Japan. Materials and Methods: A total of 321 participants were included. Participants completed a questionnaire regarding lifestyle changes, including diet, physical activity, and living and working conditions during the COVID-19 pandemic. The change in hemoglobin A1c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“… 18 reported that HbA 1c levels significantly decreased in the unstressed group, whereas Terakawa et al . 28 suggested a relationship between the worsening of glycemic control and living and working environments. Final conclusions for the change in HbA 1c during the COVID‐19 pandemic could not be drawn from these retrospective studies, including the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 18 reported that HbA 1c levels significantly decreased in the unstressed group, whereas Terakawa et al . 28 suggested a relationship between the worsening of glycemic control and living and working environments. Final conclusions for the change in HbA 1c during the COVID‐19 pandemic could not be drawn from these retrospective studies, including the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in behavioral patterns had a significant impact on the self-management of diabetes. Due to lifestyle restrictions, body weight gain, reduced physical activity, and changes in eating habits affected glycemic control (5)(6)(7)(8)(9). Table 1 summarizes the results of past studies conducted to monitor changes in hemoglobin A1c (HbA1c) and body weight before and during the COVID-19 pandemic.…”
Section: Diabetes Management Taking Into Consideration the Lifestyle ...mentioning
confidence: 99%
“…The effects of lifestyle changes on glycemic control during the COVID-19 pandemic in patients with diabetes (n = 321) were studied at our institution (5). The overall HbA1c levels showed no significant difference before and during the COVID-19 pandemic.…”
Section: Diabetes Management Taking Into Consideration the Lifestyle ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the emergence of the severe acute respiratory syndrome–associated coronavirus 2 virus at the end of 2019 affected daily life worldwide, especially regarding physical activity, with reports of decreased physical activity in various countries compared with pre-coronavirus disease 2019 (COVID-19) pandemic levels [ 13 , 14 , 15 ]. Although the COVID-19 pandemic has been reported to have no effect on glycated hemoglobin in diabetic patients, there is a relationship between decreased physical activity and increased glycated hemoglobin caused by telecommuting [ 16 ]. In fact, it has been reported that the amount of physical activity in diabetic patients is decreasing [ 17 ], and it is not certain what the long-term effects will be.…”
Section: Introductionmentioning
confidence: 99%